Posterior vaginal wall Gartner's duct cyst - Ripan Bala; Madhu Nagpal; Manmeet Kaur; Harmanpreet Kaur (Wolters Kluwer Medknow Publications, 2015)
Cyst of posterior vaginal wall is very rare. This case relates to a patient who presented with polypoidal mass protruding out from vagina which could have been easily mistaken as uterovaginal prolapse, but appropriate clinical evaluation supported with investigations clinched the diagnosis easily.